Capacity and secrecy analysis of URLLC channels subject to Lomax fading - Kapucu, Nuri (International journal of electronics and communications, 2025)
This work analyzes the capacity and physical layer security of ultra-reliable low-latency communication (URLLC) channels subject to Lomax fading. First, an analytical closed-form expression is derived for the average channel capacity of a single-input and single-output wireless communication system over Lomax fading channels. Then, closed-form expressions are proposed for secrecy outage probability and probability of positive secrecy capacity of a three node wiretap communication system operating over Lomax fading channels. All proposed expressions are simple and easy to evaluate as they involve built-in special functions available in widely used software tools such as Mathematica and MATLAB. The results are presented for various parameter values and compared to Rayleigh fading case. Finally, the analytical findings of this work exhibit an excellent agreement with both the exact numerical integration results and simulation results.